Respecting Choices® and Related Models of Advance Care Planning: A Systematic Review of Published Evidence - MacKenzie, Meredith A. (Am J Hosp Palliat Care, 2017)
All individuals should receive care consistent with their expressed preferences during serious and chronic illnesses. Respecting Choices® is a well-known model of advance care planning (ACP) intended to assist individuals consider, choose and communicate these preferences to health care providers. In this systematic review, we evaluated the published literature on the outcomes of the Respecting Choices® and derivative models utilizing criteria developed by the Cochrane Collaborative. Eighteen articles from 16 studies were included, of which nine were randomized control trials, six were observational and one was a pre-posttest study. Only two specifically included a minority population (African American). Fourteen were conducted in the United States, primarily in the Wisconsin/Minnesota region (n=8). Seven studies examined the Respecting Choices® model, while nine examined derivative models. There was significant heterogeneity of outcomes examined. We found that there is a low level of evidence that Respecting Choices® and derivative models increase the incidence and prevalence of Advance Directive and Physician Orders for Life-Sustaining Treatment (POLST) completion. There is a high level of evidence that Respecting Choices® and derivative models increase patient-surrogate congruence in Caucasian populations. The evidence is mixed, inconclusive and too poor in quality to determine whether Respecting Choices® and derivative models change the consistency of treatment with wishes and overall healthcare utilization in the end of life. We urge further studies be conducted, particularly with minority populations and focused on the outcomes of preference-congruent treatment and health care utilization.